Literature Review : The Application of High-Performance Liquid Chromatography (HPLC) in the Analysis of Pharmaceutical Compounds - Verna Wimala Salsabila; Elina Jatindria; Rimadhyna Widya Khairunissa; Athaya Wijdan Pascadiksa; Elvina Putri Rahmawati; Nur’Aini Hidayati; Aldo Octavian Ramadhan Saputra; Djustike Maylasari (INDOGENIUS, 2026)
High Performance Liquid Chromatography (HPLC) is an essential analytical technique used for the separation, identification, and quantification of compound within complex mixtures.This review article examines several research studies discussing the application of HPLC in drug analysis. This review provide an overview of HPLC utilization across various studies, including its technical advantages, analytical challenges in diverse matrices, differences in column and mobile phase selection, variations in sample preparation techniques, detector performance, the influence of flow rate, analytical parameter quality, and method validation evaluation across different drug classes. This review is expected to provide a comprehensive understanding of HPLC application in pharmaceutical analysis and important considerations in developing accurate and reliable analytical methods.